Penyelenggaraan Perlindungan Anak dalam Perda Kota Surabaya No. 6 Tahun 2011 Perspektif Maqasid Al-Shari’ah - Ulya, Zakiyatul (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2020)
Regional Regulation (Perda) of Surabaya No. 6 of 2011 concerning the Implementation of Child Protection. It contains provisions regarding children and their obligations, the implementation of child protection, and the obligations of parents, families, communities, and local governments towards them including child labor in informal sector work, community, and private sector participation, Child-Friendly City Task Force, prohibition, guidance and supervision as well as administrative, investigative, and criminal sanctions. The implementation of Regional Regulation related to child protection in Surabaya City, by Regulation No. 6 of 2011 is in accordance with maqasid al-shari'ah based on the five main elements which are the objectives of the legal designation, even though in the regional regulation, hifz al-din and hifz al-mal get a smaller portion of the setting and a different degree of clarity than the other three components. Therefore, there must be a balanced aspect of five legal objectives in the regional regulation of child protection to work optimally. Apart from that, there should also be clearer regulations, especially regarding the protection of religion and children's property so as not to create different interpretations from policy implementers and other interested parties.